LEARNING GRAMMAR THROUGH PHYSICAL GAMES - Prihhartini, Sya'baningrum (Sukma: Jurnal Pendidikan, 2018)
This study aims to investigate the language output resulted from physical games played as a practice to learn grammar. 20 university students were involved in a game in which they had to jump and throw a marker towards cue cards that contained questions in If-Conditional Type II structure. The students’ language output during the game was recorded and analyzed qualitatively. The result shows that physical game facilitates the learners to acquire new grammartical items and that it is effective to a good extent.Keywords : physical games, grammar, accuracy